Profil Pembelajaran Karakter Di Sekolah Dasar (Studi Kasus Pada Sekolah Dasar Di Kota Sampang) - Hamzah, Amir (Jurnal Inovasi dan Teknologi Pembelajaran, 2016)
Abstract: The purpose of this study was to describe the implementation of character learning in the elementary school in Sampang to find out the lesson profile to be able to give a clear picture of the issues facing so that it can help to give the offer solutions. This study implemented a case study to describe and explain the terms related to the problem of learning the characters in elementary school by exploration on learning activities and learning-related characters, both conducted in the classroom and outside the classroom, where the focus is directed on the conditions of learning and learning strategies characters used in elementary school in Sampang. Its type is an intrinsic case study that is due to the desire of the researcher to understand certain cases in all aspects and specificity of its simplicity, led to the selection of the objects examined, rather than on methodological choice. The purposes of this study were to describe the character of learning profiles in elementary schools in Sampang, consists of: (1) the purpose of learning the characters, (2) the constraints faced in the implementation of learning the characters, (3) the characteristics of the students that there are elementary schools with regard to learning character, (4) learning content organizing strategy character, (5) the character of learning materials delivery strategies, and (6) the character of learning material management strategies. The findings showed character profile learning in primary schools in Sampang, that: (1) learning objectives listed in the "RPP character" administrative only because it has no relevance to the learning process and outcome, (2) generally refers to the creation of the learning objectives 18 characters set curriculum development center, (3) the obstacles faced are personnel and financial constraints (4) in general, there are two characteristics of the students, the quality identified on the basis of socio-economic backgrounds of learners and the community, (5) there is no material learning character so there was no strategi organizing of content (6) delivery of content strategy used was lecture, giving examples of direct and conditioning, (7) use the learning management strategies learning by doing, in which the method of giving examples of dominating at every learning activity, in addition to lecturing and giving the task.